Cervical lymph node metastasis of porocarcinoma - Philipp Becker; Andreas Pabst; Andrea Schmid; John Rudat; Gunnar Müller; Richard Werkmeister (Elsevier, 2021)
Facial porocarcinoma is representing an extremely rare entity. These dermal adnex carcinomas can develop from a benign inconspicuous nodule, the poroma. We report about a patient who showed a cervical lymph node metastasis six months after excision of a cervical porocarcinoma. A B-cell lymphoma was also diagnosed during staging using FDG PET-CT. The therapy consisted of an ipsilateral neck dissection and an adjuvant radiotherapy. In the case of such rare findings, an intensive literature research followed by an interdisciplinary case discussion taking into account the patients' general health is crucial for the prognosis.